UPLC-QTOF-MS-guided isolation of anti-COPD ginsenosides from wild ginseng. Issue 66 (26th November 2019) - Zhu, Hailin; Liu, Junli; Lin, Hongqiang; Zhang, Ying; Yang, Na; Zhou, Baisong; Wang, Zhongyao; Chen-Yu Hsu, Alan; Liu, Jinping; Li, Pingya
Abstract : Four previously undescribed ginsenosides, along with five known analogues were isolated from wild ginseng by a UPLC-QTOF-MS-guided fractionation procedure. Abstract : Four previously undescribed ginsenosides, along with five known analogues were isolated from wild ginseng by a UPLC-QTOF-MS-guided fractionation procedure. Their structures were elucidated on the basis of spectroscopic and spectrometric data (1D and 2D NMR, HR-ESI-MS). The isolated compounds could significantly inhibit the cigarette smoke extract (CSE)-induced inflammatory reaction in A549 cells. The HDAC2 pathway might be involved in the protective effect against the CSE-mediated inflammatory response in A549 cells.